2021
DOI: 10.3390/plants10040643
|View full text |Cite
|
Sign up to set email alerts
|

Plant Biostimulants from Cyanobacteria: An Emerging Strategy to Improve Yields and Sustainability in Agriculture

Abstract: Cyanobacteria can be considered a promising source for the development of new biostimulants as they are known to produce a variety of biologically active molecules that can positively affect plant growth, nutrient use efficiency, qualitative traits of the final product, and increase plant tolerance to abiotic stresses. Moreover, the cultivation of cyanobacteria in controlled and confined systems, along with their metabolic plasticity, provides the possibility to improve and standardize composition and effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(59 citation statements)
references
References 159 publications
0
58
1
Order By: Relevance
“…Only the local coralloid roots were applied in each garden, and 15 mL of the slurry was buried in each hole. Applying cyanobacteria or extracts from cyanobacteria to the base of plants is a common form of exploiting the benefits of cyanobacteria for plant health [25]. The north garden site consisted of shallow cobbly clay loams that formed in sediments that overlie coralline limestone (clayey, gibbsitic, nonacid, isohyperthermic, Lithic Ustorthents) [26].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Only the local coralloid roots were applied in each garden, and 15 mL of the slurry was buried in each hole. Applying cyanobacteria or extracts from cyanobacteria to the base of plants is a common form of exploiting the benefits of cyanobacteria for plant health [25]. The north garden site consisted of shallow cobbly clay loams that formed in sediments that overlie coralline limestone (clayey, gibbsitic, nonacid, isohyperthermic, Lithic Ustorthents) [26].…”
Section: Methodsmentioning
confidence: 99%
“…Only the local coralloid roots were applied in each garden, and 15 mL of the slurry was buried in each hole. Applying cyanobacteria or extracts from cyanobacteria to the base of plants is a common form of exploiting the benefits of cyanobacteria for plant health [25].…”
Section: Methodsmentioning
confidence: 99%
“…Recently, cyanobacteria have gained considerable attention as beneficial bioagents based on their ability to produce biomass for biofertilizers to be used in sustainable farming [18,50,118]. These organisms have been considered beneficial to soil fertility and crops through their ability to fix atmospheric nitrogen solubilize phosphate [119], produce bioactive substances, such as hormones (auxins, gibberellins, cytokinins) [120], polypeptides, amino acids [121], polysaccharides [122], and siderophores [123], having stimulatory effects on plants.…”
Section: Biostimulant Effectsmentioning
confidence: 99%
“…As reported by the Scopus ® database (Figure 1b), scientific reports on cyanobacteria primarily cover the agricultural and biological sciences topic area, although some topic areas may overlap. More specifically, most articles refer to the biostimulant effect, as these microorganisms are a source of macro-and micronutrients, bioactive molecules, and plant hormones that may positively influence the plant [18]. More recently, only a few dozen articles referring to the effect of cyanobacteria on plant pathogens were cited in the Scopus database (search for "cyanobacteria + versus + plant pathogens").…”
Section: Introductionmentioning
confidence: 99%
“…The Cyanobacteria could be affecting B. hybridum growth in the invaded range through fixation of dinitrogen or through the substances it produces. A recent literature review by Santini et al (2021), found that Cyanobacteria are rich in auxin and auxin-like compounds, which act as biostimulants in plants. These biostimulants result in increased root mass and elongation and increased plant nutrient uptake.…”
Section: Hypothesismentioning
confidence: 99%